Employment and economic entities in the Polish financial sector from 2005-2016 - Grzywińska-Rąpca, Małgorzata; Markowski, Lesław (Zatrudnienie i podmioty ekonomiczne w polskim sektorze finansowym w latach 2005-2016, 2018)
The article analyzes employment in the financial sector and entities conducting financial, insurance or other activities. The aim of this study is to examine employment in the financial sector at the level of provinces and registered entities of this sector using multidimensional methods of statistical analysis. The results of the classification indicate the geographical division of the country in terms of the number of financial and insurance companies. However, the high slope of the directional coefficient means a very strong, growing tendency for the Mazowieckie voivodship, characterized by a much slower trend for the Dolnośląskie, Pomorskie and Śląskie voivodships. In fact, for most of the provinces, trends indicate a statistically significant, negative development trend for the analyzed phenomenon from 2005-2016
Econometrics = Ekonometria, 2018, Vol. 22, No. 1, s. 79-93
Keywords: financial sector; employment; economic entities; k-means method; trends; sektor finansowy; zatrudnienie; podmioty gospodarcze; metoda k-średnich; trendy